Case Report: An Anomalous Left Hepatic Venous Connection in a Patient With Unexpected Cyanosis - Luo, Fanyan; Bu, Haisong (Frontiers in Pediatrics, 2021)
An Anomalous Left Hepatic Venous (LHV) Connection is an extremely rare cardiac malformation and left hepatic venous route abnormalities not associated with other cardiac lesions do not require surgical treatment because they are physiologically benign. However, when venous route abnormalities exist with associated cardiac lesions, the conduct of the cardiac surgical repair must accommodate the abnormal venous anatomy, especially in total cavopulmonary connection patients. Herein, we present a rare case of a 7-year-old Chinese boy status post the bilateral superior vena cava pulmonary anastomosis for about one year presented with severe cyanosis, and referred to our department. However, patient showed an unexpected gradual decrease in blood oxygen saturation to 60%-70% after the extracardiac total cavopulmonary connection (ETCPC) operation. Emergency echocardiography and computed tomography conﬁrmed that LHV entered into the right atrium. Subsequently, the patient was referred to intra-atrial tunnel. This illustrative report highlights the essence of improving the preoperative accurate diagnosis to avoid unplanned reoperation in China, especially for the remote rural areas of eastern countries where the level of health care and services is relatively backward. Failure to identify anomalous LHV connection, in this case, will delay effective treatment past optimal treatment time.